Special statistics of the modern methods of contraception in the federal districs of Russian Federation - Z Z Tokova; V N Prilepskaya; A S Gata; A A Kuzemin (IP Berlin A.V., 2016)
Here are materials on the prevalence of modern contraceptive methods in the federal districts of Russian Federation.